Pulmonary Nuclear protein in Testis (NUT) carcinoma: clinical, molecular characteristics, and treatment strategies - Jingjing Qu; Zhen Chen; Yanping Zhu; JinYan Huang; Qian Shen (BMC Cancer)
Abstract Background Pulmonary nuclear protein in testis (NUT) carcinoma is a rare and aggressive malignancy that often exhibits clinical and pathological features overlapping with other thoracic malignancies, posing significant challenges for accurate diagnosis and leading to poor treatment outcomes. Method We conducted a retrospective analysis of five patients diagnosed with pulmonary NUT carcinoma between 2020 and 2023. Comprehensive clinical, imaging, histopathological, and molecular data and survival outcomes were collected. Results The cohort included three females and two males, with a median age of 44 years. Clinical features commonly involved centrally located masses with mediastinal invasion. Distant metastases to bones, pleura, and lungs were confirmed in 60% of cases. Diagnostic confirmation was achieved through NUT protein positivity via IHC and FISH rearrangements in all five patients. RNA sequencing identified BRD3-NUTM1 fusions in 60% (3/5) patients. Chemotherapy was employed as the initial treatment strategy but showed limited efficacy in advanced stages. Among two patients undergoing surgical resection, better outcomes were achieved in the patient receiving adjuvant therapy with overall survival (OS) exceeding 36 months. Immunotherapy demonstrated limited benefit, likely attributable to low PD-L1 expression and an immunologically “cold” tumor microenvironment. Despite multimodal treatment approaches, three out of five patients in advanced pulmonary NUT carcinoma died to the disease, with OS ranging from 6 to 15 months. Conclusion Advanced molecular techniques are critical for diagnosing pulmonary NUT carcinoma, but survival outcomes remain poor. Surgical resection with adjuvant therapy offers better outcomes for early-stage patients, while chemotherapy and immunotherapy show limited efficacy in metastatic cases due to the tumor’s aggressive behavior. Early detection and innovative therapies are essential for improving outcomes.